What set me free : a true story of wrongful conviction, a dream deferred, and a man redeemed - Banks, Brian, 1985-; Dagostino, Mark (Atria Paperback, 2019)
At age sixteen, Brian Banks was a nationally recruited All-American Football player, ranked eleventh in the nation as a linebacker. Before his seventeenth birthday, he was in jail, awaiting trial for a heinous crime he did not commit. Although Brian was innocent, his attorney advised him that as a young black man accused of rape, he stood no chance of winning his case at trial. Especially since he would be tried as an adult. Facing a possible sentence of forty-one years to life, Brian agreed to take a plea deal<U+2014>and a judge sentenced him to six years in prison. At first, Brian was filled with fear, rage, and anger as he reflected on the direction his life had turned and the unjust system that had imprisoned him. Brian was surrounded in darkness, until he had epiphany that would change his life forever. From that moment on, Brian made the choice to shed the bitterness and anger he felt, and focus only on the things he had the power to control. He approached his remaining years in prison with a newfound resolve, studying and applying spirituality, improving his social and writing skills, and taking giant leaps on his journey toward enlightenment. When Brian emerged from prison with five years of parole still in front of him, he was determined to re-build his life and finally prove his innocence. Three months before his parole was set to expire, armed with a shocking recantation from his accuser and the help of the California Innocence Project, the truth about his unjust incarceration came out and he was exonerated. Finally free, Brian sought to recapture a dream once stripped away: to play for the NFL. And at age twenty-eight, he made that dream come true.